2019
DOI: 10.1136/archdischild-2019-316945
|View full text |Cite
|
Sign up to set email alerts
|

Potentially preventable hospitalisations in children: a comparison of definitions

Abstract: ObjectiveTo compare admission rate, cumulative incidence and social distribution of potentially preventable hospitalisations (PPHs) among children according to the current Australian adult definition, and the child definition developed in New Zealand.Design, setting, participantsDeidentified, linked public hospital, births registry and perinatal data of children aged 0–10 years born 2002–2012 in South Australia (n=1 91 742).Main outcome measuresPPH admission rates among 0–10 year olds and cumulative incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The organization follows best practice guidelines which initially include deduplication processes and deterministic linkage, followed by probabilistic linkage using industry-leading algorithms, and with detailed clerical review. In a recently published paper using data from SA-NT DataLink, it was stated that Australian data linkage systems estimate linkage error rate at approximately 0.1%–0.5% (Procter et al, in press). The data sets made available to the researchers included child protection data from the SA Department for Child Protection (DCP), child birth information from the SA Births Registry and the SA Perinatal Statistics Collection, and education data from the SA Department for Education (DfE).…”
Section: Methodsmentioning
confidence: 99%
“…The organization follows best practice guidelines which initially include deduplication processes and deterministic linkage, followed by probabilistic linkage using industry-leading algorithms, and with detailed clerical review. In a recently published paper using data from SA-NT DataLink, it was stated that Australian data linkage systems estimate linkage error rate at approximately 0.1%–0.5% (Procter et al, in press). The data sets made available to the researchers included child protection data from the SA Department for Child Protection (DCP), child birth information from the SA Births Registry and the SA Perinatal Statistics Collection, and education data from the SA Department for Education (DfE).…”
Section: Methodsmentioning
confidence: 99%
“…15 A higher proportion of IWC children experienced a PPH which are also associated with socioeconomic disadvantage. 40 While IWC children were more likely to experience a hospitalisation relating to a CCC, the overall proportion was small (age 11-15 years: 1.9%; age 16-20 years: 2.2%).…”
Section: Discussionmentioning
confidence: 88%
“…While welfare receipt has been associated with poorer mental health outcomes, 11,24,26,29 our study showed IWC children experience even higher mental health hospitalisation rates compared to WC experienced only in one generation. We expected IWC children to have higher injury hospitalisation rates given injury hospitalisation is more frequent in children from the most disadvantaged backgrounds 40,41 but this had not been quantified before. IWC children having higher hospitalisation rates related to pregnancy and childbirth reflects the inclusion of welfare payments associated with parenting.…”
Section: All Cause Hospitalisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important health outcome is hospitalisations for conditions considered potentially avoidable with the provision of ‘timely and adequate non-hospital care’ (p375) 9. Examples of these conditions include respiratory conditions, gastrointestinal disease and vaccine-preventable diseases 10 11.…”
Section: Introductionmentioning
confidence: 99%